Incidencia e identificación de plagas en tres clones de cacao, cultivados con dos niveles de sombra y dos niveles de fertilización en el Padmi, provincia de Zamora Chinchipe - Ortega Mora, Dayanna Michelle (2022)
The cocoa crop is of great economic importance for Ecuador, due to its organoleptic characteristics it is appreciated worldwide. There are 601 000 ha planted with cocoa and the province of Zamora Chinchipe has 1 110 ha under cultivation. Due to poor management of shade and fertilization or according to the clone in cocoa plants; it can have a very important effect on the growth and productivity of the cocoa plantation during its development. The concern has always been to obtain improved varieties with high yields and desirable characteristics of health and quality, thus generating better benefits for producers. For this reason, it was proposed to evaluate the affectation of existing pests in cocoa under two levels of shade, two levels of fertilization and in three types of clones in the province of Zamora Chinchipe, at the Padmi Experimental Station of the National University of Loja. A completely randomized design was applied; with twelve treatments, being the experimental unit a cocoa tree. The 48 plants were checked every twenty days during five months, where the insect pests present were evaluated and identified, and the percentage of damage by herbivorous insects on each plant was recorded. A generalized linear model (GLM) with Gaussiano error and logarithmic-link function was used to determine the influence of pests on shade levels, fertilization and clone type, and Excel was used, and to determine abundance and richness, each individual was counted. Throughout the evaluation of the project, a total of 14 species belonging to three orders and nine different families were collected, of which only two species could be identified, the rest were identified to genus level except for the Hemiptera specimens, which remained only to family level; the population with the highest number of specimens were those belonging to the order Orthoptera followed in quantity by the order Coleoptera and Hemiptera. A significant effect was observed in the type of clone, according to their order of affectation from highest to lowest were EETP-800, EETP801, and CCN51, but not in the shade or nutrition separately, only a significant interaction of treatments without shade and without nutrition was analyzed. Key words: Cocoa, shade, fertilization, clone, insects, pests.